MODEL KERJASAMA BAGI HASIL DENGAN METODE “KEDOK” PADA PETANI PADI PEMILIK DAN PETANI PADI PENGGARAP (Studi Kasus Pada Petani Padi Pekon Mulyorejo Kecamatan Banyumas Kabupaten Pringsewu) - Lukman Hidayat; Anam Miftakhul Huda; Nur Ika Mauliyah (Universitas PGRI Madiun, 2019)
This research was conducted in Pekon Mulyorejo, Banyumas District, Pringsewu Regency with the object of research by rice farmers. This study aims to determine how the behavior of farmers in Pekon Mulyorejo regarding the financing and management and calculation of the benefits of rice farmers. The type of research used is qualitative research using the phenomenology approach. Phenomenology aims to describe the meaning of life experiences experienced by several individuals, about certain concepts or phenomena, by exploring the structure of human consciousness. So here the researchers want to know the meaning of the experience experienced by farmers and rice farm workers related to the calculation of income by the kedok method through this phenomenology study. Data were obtained by interviewing techniques then the results of the interviews were then analyzed to find out how accounting and local wisdom in the profit sharing system between rice farmers and rice farmers were cultivated by the kedok method. Based on the research results obtained from analyzing the results of experience and interviews with rice farmers in Pekon Mulyorejo produce a form or model of profit sharing cooperation with the method of